Inovasi Pangan Lokal: Pelatihan Pembuatan Keripik Umbi Eleocharis Dulcis untuk Kemandirian Ekonomi di Desa Domas - Haki, Ubay; Jumhana, Enjum; Prahastiwi, Eka Danik (Al-DYAS, 2025)
This study aims to develop training for making chips from Eleocharis dulcis (suge) tubers as an effort to enhance the economic independence of the community in Domas Pontang Village, Serang Regency. The training approach used is the Learning Cycle 3E (Engagement, Exploration, Explanation) to improve participants' understanding and skills in processing Eleocharis dulcis tubers into value-added products. This training method is designed to provide hands-on experience for participants, facilitate the exploration of creative ideas, and offer technical explanations related to the effective and efficient process of making chips. The study's results are expected to enhance the community's skills in processing local raw materials into marketable products, thereby promoting economic independence through increased income from local product-based businesses. Furthermore, this study has the potential to introduce Eleocharis dulcis chips as an alternative healthy and nutritious food product for the community.